Opinion of the People on the Ferry Service in Luang Prabang District, Luang Prabang - XOUMPHONPHACKDY, NAKAZU (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims to 1) examine the behavior of people who use ferry crossing services in Luang Prabang City, 2) investigate the level of public opinions toward the use of ferry crossing services in Luang Prabang City, Luang Prabang Province, 2) and compare public opinions regarding the use of ferry crossing services in Luang Prabang City, Luang Prabang Province, classified by personal factors. This research adopts a quantitative research approach and employs a survey method with a sample of 410 respondents. Data were collected using a questionnaire and analyzed using descriptive statistics as frequency, percentage (%), mean ( ), and standard deviation (SD) and inferential statistics, including the Independent-Samples t-test and One-Way ANOVA. The research findings revealed that 1) Regarding user behavior, most users of the ferry crossing service in Luang Prabang City, Luang Prabang Province, reported using the service more than four times, with daily usage being common. The majority spent no more than approximately 10 minutes traveling from their homes, workplaces, or other locations to access the service. The peak periods of service use were 08:01–12:00 and 06:01–08:00, and the primary purposes for using the ferry crossing service were commuting to work and attending school; 2) With respect to public opinions, users of the ferry crossing service in Luang Prabang City, Luang Prabang Province, demonstrated an overall very high level of positive opinion toward the service; 3) The comparison of public opinions toward the use of the ferry crossing service, classified by personal factors, indicated that age, occupation, and educational level were the only factors showing statistically significant differences in opinion levels regarding service use. These differences were significant at the 0.05 level (p < 0.05).